Can We Improve Vaccine Efficacy by Targeting T and B Cell Repertoire Convergence? - Fink, Katja (Frontiers in Immunology, 2019)
Vaccine development is based on the assumption that healthy individuals have near unlimited repertoires of B cells and T cells that are theoretically able to recognize every protein or glycoprotein antigen. However, there might be “holes” in the repertoire where no B or T cell is able to bind to a given antigen, particularly if that antigen has a limited number of epitopes. In those cases, repertoires could be a limiting factor for the efficacy of vaccines. Assuming that it is possible to predict which B and T cell receptors will be engaged by a given immunogen, vaccine responsiveness could be predicted and vaccine strategies could be optimized and personalized. In addition, testing of protective responses after vaccination could be simplified enormously if protective responses could be reliably predicted based on BCR and TCR sequence motives that are specifically selected after immunization. Bulk sequencing technology has shown evidence of converging sequences (antigen-specific sequences found independently in multiple individuals) after infection or vaccination. However, only single cell technologies have made it possible to capture both heavy and light chain of a B cell receptor or both alpha and beta chain of a T cell receptor, allowing the cloning of receptors and the functional validation of a predicted specificity. This review summarizes recent published evidence of validated converging sequences for infectious diseases and discusses current and future implications for vaccine research.